Pendampingan Pastoral Bagi Perempuan Sebagai Orang Tua Tunggal - Margery M Wenno (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2021)
A single parent, according to its literal meaning, is a person who takes care of a living and raises their child without a partner.  Women giving birth out of wedlock has become a cross-border phenomenon.  Occurs in the church community as well as in the community with various beliefs and backgrounds. Women who become single parents need assistance in dealing with every problem. Women as single parents go through various problems from psychological aspects, socio-cultural, economic and religious. With pastoral studies, research found that there is support from the church for women who become single parents in the form of pastoral assistance, in the end women who become single parents can face and find meaning in their life as single parents and can make decisions to live a better life.